Cash collection & transmission - Coyle, Brian; Chartered Institute of Bankers (Canterbury : CIB Publishing, 2000)
Explains how money transmission systems have developed and how each works.
Series statement on jacket.
Includes index.
oif 28/01/15; 19/03/15
Loan
Keywords: Banks and banking; Money; Electronic funds transfers; Cash management; Collecting of accounts